PENGARUH INISIASI MENYUSU DINI TERHADAP PERUBAHAN SUHU TUBUH BAYI BARU LAHIR DI BPM â€œYâ€ KOTA BUKITTINGGI TAHUN 2015 - Ashra, Fauzi; Rina, Rina (LPPM Universitas Prima Nusantara Bukittinggi, 2017)
Â Patients in intensive space have the right to get special attention due to metabolic changes that have an impact on nutritional status. Critical patients will experience an increase in metabolism as the body's response to disease. Assessment of nutritional status must be carried out routinely in the hospital, including in the ICU. The Council of Europe 2001, that there are no nutritional assessment standards that can be used for all patients treated. The assessment must be early, simple, based on current science and can be adapted in the clinical environment. The American Society of Parenteral and Enteral (ASPEN) recommends assessing nutritional status or nutritional screening tools in patients treated by using Subjective Global Assessment (SGA). Another measure of nutritional status assessment that can be used is the Malnutrition Screening Tools (MST). MST is a nutritional status assessment tool that has been used by the General Intensive Care Unit (ICU) in Achmad Mochtar Bukittinggi Hospital. This study aims to analyze the differences in the accuracy of MST and SGA in assessing nutritional status as well as differences in sensitivity of MST and SGA as indicators of the incidence of pressure sores in patients in the ICU of the Achmad Mochtar Bukittinggi Hospital. The type of this research is this research is quantitative research with comparative hypothesis type and cross-sectional research design. The results of this study indicate that SGA is more accurate in assessing nutritional status in patients in intensive rooms.